THE EFFECTS OF BALANCED SCORECARD IMPLEMENTATION: THE CASE OF A MALAYSIAN SERVICE ORGANIZATION FROM INTERNAL BUSINESS PROCESSES PERSPECTIVE (Journal of Technology and Operations Management, 2016)
The objective of this research was to investigate the impact of the employees’ attitude derived from the usage of Balanced Scorecard (BSC) Internal Business Processes perspective in MGSB Service Organization. Other objectives include recommendations to improve existing performance management system (PMS) practices and to identify issues and challenges in its implementation which merits further research. A total of 1000 respondents were surveyed and the data was analysed using Pearson Correlation Analysis and Regression Analysis. Analysis of results indicated that there was a positive relationship between the Organizational Culture and Employee Attitude in MGSB. The implication of this research would benefit the organization in terms of employees’ effectiveness and the pervasiveness of the performance metric implementation.